Pengaruh Implementasi Konsep Tarbiyah Dan Keteladanan Guru Terhadap Pembentukan Akhlak Siswa Di Madrasah Tsanawiyah An-Nur Makassar - Nuraeni Nuraeni; Abdul Rahman (Jurnal Ilmiah Multidisiplin Mahasiswa dan Akademisi, 2026)
This study aims to examine the influence of the implementation of the tarbiyah concept and teachers' role modeling on the moral character development of students at Madrasah Tsanawiyah An-Nur Makassar. The study employed a quantitative approach using a survey method. The research population consisted of all students of Madrasah Tsanawiyah An-Nur Makassar, with the entire population selected as the sample through a saturated sampling technique. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. The data were analyzed using multiple linear regression. The findings indicate that the implementation of the tarbiyah concept has a positive and significant effect on students' moral character development, with a regression coefficient of 0.430 and a significance value of 0.002 (p < 0.05). Teachers' role modeling also has a positive and significant effect on students' moral character development, with a regression coefficient of 0.382 and a significance value of 0.004 (p < 0.05). Simultaneously, the implementation of the tarbiyah concept and teachers' role modeling significantly influence students' moral character development, as indicated by an F-value of 14.053 and a significance value of 0.000 (p < 0.05). The coefficient of determination (R²) of 0.305 indicates that both independent variables explain 30.5% of the variance in students' moral character development, while the remaining 69.5% is influenced by other factors beyond the scope of this study. This study concludes that the implementation of the tarbiyah concept and teachers' role modeling are essential factors in fostering students' moral character. Therefore, strengthening the implementation of tarbiyah and enhancing teachers' exemplary conduct should become key strategies for promoting character education in Islamic secondary schools.